CAROLINA SUNSET, CUBAN SUNRISE: CONTINUITY, CHANGE, AND HISTORIC INTERSECTIONALITY IN CUBA AND THE UNITED STATES - Walls, Eric A (East Carolina University, 2020)
Reconstruction twisted the foundations of race, class, and gender in the southern United States into knots. The changes that created a new socio-political paradigm in the aftermath of the Civil War, especially emancipation and the attempts to provide African Americans with the rights of full citizenship, were so alien to the white Southern worldview and conceptions of self that some, like Harriet Rutledge Elliott Gonzales and Eliza Ripley McHatton, questioned whether they could or should remain in a South so different from the one they previously knew. For such women, these changes so upset their own conceptions of self that they not only willfully, but eagerly chose to escape the home they knew and loved all their lives to try to re-establish a sense of normalcy in a new land as soon as the opportunity presented itself. The key to that, however, was finding a place that was similar enough in its social dynamic that Southerners like them could, at least to some degree, reclaim their sense of self and forge a life and a lifestyle that they found comfortable. For Hattie and Eliza, Cuba represented just such a place. The socio-political upheaval of the Civil War and Reconstruction challenged elite Southern women's deep seated antebellum ideals of race, class, and gender, which led to a crisis of identity for women like Harriet Rutledge Elliott Gonzales and Eliza Ripley McHatton, and highlighted the relative homogeneity of the slave/plantation regime, and its associated hierarchies of race, class, and gender, across cultures and borders within the Atlantic World.
Keywords: Americans--Cuba--History; Southern States--Social conditions--1865-1945; Women--Social conditions; Ripley, Eliza, 1832-1912